Basic Consideration for Facial Aging: Analyses of the Superficial Musculoaponeurotic System Based on Anatomy. (11th November 2020) - Okuda, Itsuko; Akita, Keiichi; Komemushi, Takayoshi; Irimoto, Masahiro; Nakajima, Yasuo
Abstract: Background: The superficial musculoaponeurotic system (SMAS) is an important structure to understand for face-lift surgeries. However, the detailed distribution and imaging findings of the SMAS have not been established yet. Objectives: The aim of this study was to establish the accurate distribution and computed tomography (CT) imaging findings of the SMAS based on cadaveric studies. Methods: This study was designed in a 3-step procedure. First, 7 cadaver faces were utilized to understand the distribution and histology of the SMAS. Second, the SMAS findings from the cadaveric studies were compared with the CT images. Third, CT images were enrolled for the SMAS interpretation. Results: In 7 cadaveric studies, the SMAS was observed as a subcutaneous fibro-membranous structure extending from the galea aponeurotica to the platysma muscle and laterally connected to the parotid fascia. On the medial side, it also connects with major and minor zygomatic muscles. The SMAS consisted of muscular fibers, collagen fibers, and elastic fibers histologically. Eighteen CT images (all females; age range, 21-82 years) showed the thin linear structures corresponding to the fibro-membranous structures in the cadaveric studies. CT density of the SMAS was similar with that of the muscle, and the SMAS was recognizable in all 18 subjects. Conclusions: The SMAS is a definite anatomical structure that can be demonstrated as a thin membranous structure on CT. This clinical application could be applicable to the development the cosmetic surgical procedures.